2014
DOI: 10.1002/humu.22569
|View full text |Cite
|
Sign up to set email alerts
|

Palindrome-Mediated and Replication-Dependent Pathogenic Structural Rearrangements within theNF1Gene

Abstract: Palindromic sequences can form hairpin structures or cruciform extrusions, which render them susceptible to genomic rearrangements. A 197-bp long palindromic AT-rich repeat (PATRR17) is located within intron 40 of the neurofibromatosis type 1 (NF1) gene (17q11.2). Through comprehensive NF1 analysis, we identified six unrelated patients with a rearrangement involving intron 40 (five deletions and one reciprocal translocation t(14;17)(q32;q11.2)). We hypothesized that PATRR17 may be involved in these rearrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…[43][44][45] Particularly, within intron 40 of NF1, a palindromic AT-rich repeat (PATRR17; 197 bp), especially the loop of the palindrome (7 bp), has been identified as an intragenic rearrangement hotspot. 41 In addition to non-B DNA structures, Alu elements were also shown in this study to be involved in recurrent genomic rearrangements. …”
Section: Nf1 Intragenic Rearrangement Hotspots Are Located Within a 1mentioning
confidence: 92%
See 4 more Smart Citations
“…[43][44][45] Particularly, within intron 40 of NF1, a palindromic AT-rich repeat (PATRR17; 197 bp), especially the loop of the palindrome (7 bp), has been identified as an intragenic rearrangement hotspot. 41 In addition to non-B DNA structures, Alu elements were also shown in this study to be involved in recurrent genomic rearrangements. …”
Section: Nf1 Intragenic Rearrangement Hotspots Are Located Within a 1mentioning
confidence: 92%
“…In addition to causing deletions, serial replication stalling also leads to insertions and translocations, further supporting a significant contribution of the replication-based mechanism to genomic rearrangements. 20,41,[53][54][55] Other studies also indicate that the high level of microhomology observed at the breakpoint junctions suggests presence of a replication-based mechanism and a mitotic origin. 20,23,30,56 Given that microhomologous sequences are widely distributed in the genome, in addition to investigating sequence context, exploring the DNA spatial proximity and 3D genomic architecture close to the junction site is likely to reveal which DNA interval is susceptible to double-strand break or replication-fork collapse, as well as the accessibility of microhomologous sequences to enzymes associated with FoSTeS/ MMBIR.…”
Section: Patrr17 Has Demonstrated Diverse Rearrangement Mechanisms Lementioning
confidence: 94%
See 3 more Smart Citations